Premarital Sex Behaviour of Adolescents in Makassar, Indonesia (Medico Legal Update, 2021)
Based on projections of the National Development Planning Agency (Bappenas) the number of populationIndonesia in 2018 reached 265 million people. The number consists of 133,17 million men and 131,88million women and 44,10 million are teenagers. The population data in South Sulawesi in 2018 was8,771,970 people and in 2015 the population of South Sulawesi was 8,520 million people and 1,56 millionpeople were teenagers. Adolescent sexual behavior, especially premarital sexual behavior, still dominatesthe debate in terms of moral, psychological, and physical. Premarital sex in adolescents is a serious problembecause it relates to the low use of contraception and adolescents tend to have more sexual partners if theystart having premarital sex at an earlier age. This article aims to find out knowledge, attitudes, actions ofpremarital sexual behavior and its relationship with the environment promiscuity in adolescents in Makassar,Indonesia. This research is an observational analytic study with cross-sectional study design. The time usedin this study is 8 months. The location of the study will be conducted in high school students 17 & 19 inMakassar, one of the Metropolitan cities in Indonesia. The population in this study is high school students17 & 19 in Makassar City as many as 200 students. In this study, researchers used the proportionate randomsampling method, a sample consists of 134 students. The analysis used in the study was the Chi-Squaretest. This study results that there was a significant relationship between premarital sex knowledge with asocial circle of friends with p-value = 0.029 and also a significant relationship between knowledge with aplace to hang out with p-value = 0.009. There was a significant relationship between premarital sex attitudeswith the social environment of friends with p-value = 0.034 and there was also a significant relationshipbetween attitudes with the place to hang out with p-value = 0.020. There is a significant relationship betweenpremarital sex behavior with the community’s social environment with p-value = 0.003.